Pengaruh Motivasi dan disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Lingkar Sakti Mas Banjarmasin - Siti Mardah; Citra Amelia; Saidilah (PT. Karya Inovatif Nusantara, 2025)
This study aims to assess the influence of Motivation and Work Discipline on Employee Performance at PT. Lingkar Sakti Mas Banjarmasin. This study uses a quantitative approach with 32 respondents, all of whom were sampled through saturated sampling techniques. The research instrument was a Likert scale questionnaire that had been tested for validity and reliability. Data analysis was performed using multiple linear regression. The results showed that Motivation (X1) had a significant effect on Performance (Y), with a calculated t value of 2.355> t table 2.042 and a significance of 0.026 <0.05. Work Discipline (X2) also had a significant effect, with a calculated t value of 3.683> t table 2.042 and a significance of 0.001 <0.05. Simultaneous test (F test) shows F count 12.310 > F table 3.328 and significance 0.000 < 0.05, which means that together Motivation and Work Discipline have a significant effect on Performance. In conclusion, improving employee performance can be achieved if work motivation and work discipline are carried out in a balanced and consistent manner.